2012
DOI: 10.1002/art.34376
|View full text |Cite
|
Sign up to set email alerts
|

DNA demethylation of CD40L in CD4+ T cells from women with systemic sclerosis: A possible explanation for female susceptibility

Abstract: Objective. Systemic sclerosis (SSc) is an autoimmune disease with a predilection for women. The interaction between CD40 and CD154 (CD40L) is known to be involved in the development of SSc. Although CD40L is overexpressed in patients with SSc, the mechanisms leading to this overexpression are not well understood. We previously demonstrated that DNA demethylation reactivates the silent X chromosome, resulting in CD40L overexpression in healthy women. We hypothesized that CD40L up-regulation by DNA demethylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(77 citation statements)
references
References 31 publications
(42 reference statements)
4
72
1
Order By: Relevance
“…Lian and colleagues evaluated the expression levels and DNA methylation within the CD40L gene, which is located on the X chromosome, in men and women with SSc compared to healthy controls. The authors demonstrated increased expression of CD40L in female SSc patients in association with demethylation of the promoter region of CD40L in CD4+ T cells [40]. This study showed that there is no difference in CD40L expression levels between male SSc patients and male controls.…”
Section: Female Sex Predominance and Cd40l Methylation Inmentioning
confidence: 85%
“…Lian and colleagues evaluated the expression levels and DNA methylation within the CD40L gene, which is located on the X chromosome, in men and women with SSc compared to healthy controls. The authors demonstrated increased expression of CD40L in female SSc patients in association with demethylation of the promoter region of CD40L in CD4+ T cells [40]. This study showed that there is no difference in CD40L expression levels between male SSc patients and male controls.…”
Section: Female Sex Predominance and Cd40l Methylation Inmentioning
confidence: 85%
“…Thus, DNA methylation results in histone deacetylation leading to the transcriptional repression of target genes through chromatin condensation. In SSc, DNA hypermethylation of the FLI1 and KLF5 genes in dermal fibroblasts (Noda et al, 2014;Wang et al, 2006) and the BMPRII gene in microvascular endothelial cells (Wang and Kahaleh, 2013) and DNA hypomethylation of the ACTA2 gene in lung fibroblasts (Hu et al, 2011) and the CD40L and CD70 genes in CD4 + T cells (Jiang et al, 2012;Lian et al, 2012) have been reported (Broen et al, 2014). Also, hypoacetylation of histone H3 and H4 in the FLI1 and KLF5 promoters is exhibited in SSc dermal fibroblasts (Noda et al, 2014;Wang et al, 2006).…”
Section: Introductionmentioning
confidence: 90%
“…CD4+ T cell hypomethylation has been shown to be associated with reduced expression of methylation-regulating genes: DNA methyltransferase-1 (DNMT1), methyl-CpG-binding domain (MBD) 3, and MBD4 [6,9,12]. Furthermore, CD40L gene promoter has been shown to be hypomethylated and transcriptionally active in CD4+ T cells [6,9,13]. In female SSc patients, the presence of demethylated CD40L regulatory elements on the inactive X chromosome leads to CD40L overexpression; these latter findings may, in part, explain the predominance of SSc in females [6,9,13]; (2) endothelial cells from SSc patients have been found to show CpG hypermethylation of the bone morphogenetic protein receptor factor type 2 (BMPR2), which may contribute to higher vulnerability of endothelial cells to apoptosis and oxidation damage [14].…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, CD40L gene promoter has been shown to be hypomethylated and transcriptionally active in CD4+ T cells [6,9,13]. In female SSc patients, the presence of demethylated CD40L regulatory elements on the inactive X chromosome leads to CD40L overexpression; these latter findings may, in part, explain the predominance of SSc in females [6,9,13]; (2) endothelial cells from SSc patients have been found to show CpG hypermethylation of the bone morphogenetic protein receptor factor type 2 (BMPR2), which may contribute to higher vulnerability of endothelial cells to apoptosis and oxidation damage [14]. Additionally, CD70 is part of the tumor necrosis factor (TNF) α superfamily and is restricted to T and B lymphocytes and mature dendritic cells [6,9,10]; in SSc patients, the promoter of CD70 is hypomethylated, leading to the overexpression of CD70 by CD4+ T cells; and (3) fibroblast global DNA hypermethylation has been found in dermal fibroblasts from SSc patients; histological analyses of skin biopsy specimens of SSc patients showed higher levels of methylation regulatory genes DNMT1, MBD1, and methyl-CpG-binding protein (MECP) 2 than controls [6].…”
Section: Introductionmentioning
confidence: 99%